2019
DOI: 10.1186/s12913-019-4140-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of doctors to hypertension clinical guidelines in academy charity teaching hospital, Khartoum, Sudan

Abstract: Background Clinical guidelines are systematically proven statements that help physicians to make healthcare decisions for specific medical conditions. Non-adherence to clinical guidelines is believed to contribute significantly to poor delivery of clinical care, and hence poor clinical outcomes. This study aimed at investigating adherence of doctors to hypertension clinical guidelines in Academy Charity Teaching Hospital, Khartoum, Sudan. Methods A cross-sectional hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This nding is lower than a nding from study in Malaysia which similarly revised medical record of patients and found 67.1% of them received guideline compliant treatment (33). It's also lower than a nding of compliance to Malaysian clinical practice guideline which indicated that two third (73.5%) of the entire treatment were in compliance with Clinical practice guideline(38), and fewer than the nding from South Africa with over all compliance of 51.9% (42). This poor compliance in the current study is because the study participants have very poor compliance to life style recommendations which is applied for only 79(20.6%) patients.…”
Section: Discussionmentioning
confidence: 56%
“…This nding is lower than a nding from study in Malaysia which similarly revised medical record of patients and found 67.1% of them received guideline compliant treatment (33). It's also lower than a nding of compliance to Malaysian clinical practice guideline which indicated that two third (73.5%) of the entire treatment were in compliance with Clinical practice guideline(38), and fewer than the nding from South Africa with over all compliance of 51.9% (42). This poor compliance in the current study is because the study participants have very poor compliance to life style recommendations which is applied for only 79(20.6%) patients.…”
Section: Discussionmentioning
confidence: 56%
“…Based on the definition used in the current study, a total of 58.9% doctors had adequate knowledge of guidelines recommendations. In comparison, the percentage of doctors who were adequately aware about recommendations of hypertension guidelines was 73% in Malaysia, [23] 51.9% in Sudan, [26] 49.1% in Kuwait, [16] 23% in Germany [25] and 20.1% in Italy. [27] In the current study, doctors' with a mean knowledge score of 7.55 + 1.73 on 11 points scale comparatively performed better than the German and Italian doctors with their respective mean knowledge score of 5.3 and 4.9.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to our finding, increase in doctors' age, senior job titles (consultant/specialist) and increased duration of clinical practice were significantly associated with their higher adherence with hypertension guidelines in studies conducted Sudan and Japan. [26,28] Likewise, a Malaysian study also found that consultants and specialists had significantly higher knowledge about recommendations of Malaysian hypertension guidelines. [23] In current study, the overwhelming majority of consultants and specialists were from cardiology and nephrology, where their likely involvement in the management of hypertension could be one of the possible reasons for their greater awareness about guidelines recommendations.…”
Section: Discussionmentioning
confidence: 96%
“…In a study by Abdelgadir et al . on adherence of doctors to HTN guideline the only variable which contribute to the adherence rate was the duration of clinical work,[ 13 ] he found no association between age or job title with adherence rate. This is in line with the results of our study as we have found that more experience is associated with adherence to the guideline but the age of physicians has no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] Different variables can influence physicians' adherence to guidelines such as lack of knowledge about the guideline or lack of agreement with recommendations, self-efficacy, environmental variables such as patients' preference[ 12 ] and also a gap in clinical governance. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%